A clinicopathological study of facial granulomatous dermatoses: A hospital-based study - Mahesh Mathur; Alina Karki; Prakash Acharya; Ayush Jha (Wolters Kluwer Medknow Publications, 2019)
Background: Granulomatous dermatoses of various types, etiologies, and clinical features frequently present with similar clinicopathological features which create a dilemma and diagnostic challenge for experts. Early diagnosis of facial lesions is of prime concern due to potential social stigma and psychological stress because of cosmetic disfigurement. Objective: To study the epidemiological and clinicopathological features of various granulomatous facial skin lesions and their concordance rate. Materials and Methods: A retrospective, hospital-based study was carried out at the Department of Dermatology, College of Medical Sciences, Bharatpur, over a period of 5 years (January 2013-January 2018). All clinically suspected cases of facial granulomatous dermatoses were included, their clinical and histological findings were recorded and analyzed according to the standard protocol, and a clinicopathological correlation was ascertained. Results: Among 850 skin biopsies performed during the study, 30 cases were clinically suspected as facial granulomatous dermatoses. There was female predominance (n = 22, 73.33%), and the mean age of patients was 41.7 years. Majority of cases (n = 29, 96.66%) were of infectious origin with leprosy as predominant cause (n = 25, 83.33%), followed by cutaneous tuberculosis (n = 4, 13.33%). Histologically, epithelioid cell granulomas (n = 26, 86.67%) and histiocytic granuloma (n = 3, 10%) were observed. Fite Faraco stain was positive in 6 (20%) cases of leprosy. An overall concordance rate of 80% was observed in facial granulomatous dermatoses in our study. Conclusion: In our study, infectious etiology is the most common cause of facial granulomatous dermatoses. Among infections, leprosy is the most common.